2022
DOI: 10.3390/ani12202828
|View full text |Cite
|
Sign up to set email alerts
|

Using Pedigree and Genomic Data toward Better Management of Inbreeding in Italian Dairy Sheep and Goat Breeds

Abstract: The inbreeding coefficient is an important parameter for livestock management. Small ruminant breeders and associations mainly rely on pedigree information, but genomic tools are gaining relevance, overcoming possible pedigree inconsistencies. This study investigates the relationship between pedigree-based and genomic inbreeding in two goat and four sheep dairy breeds. Pedigree and genomic data (medium-density SNPchip) were obtained for 3107 goats and 2511 sheep. We estimated pedigree depth (number of fully tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…It is known that in local breeds, the imputation accuracies might be overestimated mostly due to either highly structured and related population (Bolormaa et al., 2015) or due to a low effective population size (Druet et al., 2014). Although all tested breeds were limited in size, there are recent evidence that their inbreeding level is modest since all breeds except Sarda showed average inbreeding between 1% and 6% based on Runs of Homozygosity estimate (FROHfalse)$$ {F}_{\mathrm{ROH}}\Big) $$ (Cortellari et al., 2022). The Sarda breed showed an average FROH$$ {F}_{\mathrm{ROH}} $$ of 13.5%, which might partially explain, together with the highest number of animals considered in the study, why the highest concordance rate was found in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in local breeds, the imputation accuracies might be overestimated mostly due to either highly structured and related population (Bolormaa et al., 2015) or due to a low effective population size (Druet et al., 2014). Although all tested breeds were limited in size, there are recent evidence that their inbreeding level is modest since all breeds except Sarda showed average inbreeding between 1% and 6% based on Runs of Homozygosity estimate (FROHfalse)$$ {F}_{\mathrm{ROH}}\Big) $$ (Cortellari et al., 2022). The Sarda breed showed an average FROH$$ {F}_{\mathrm{ROH}} $$ of 13.5%, which might partially explain, together with the highest number of animals considered in the study, why the highest concordance rate was found in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic data aid in studying inbreeding depression without the need for extensive parentage analysis over multiple generations [55][56][57], as these two inbreeding coefficients are related [42]. While studies demonstrate a slight correlation between genomic and pedigree-based inbreeding values in Massese sheep, other breeds with more complete pedigrees show a stronger correlation between these values [58]. Genealogical data represent the primary information source for assessing genetic variability in livestock populations [59].…”
Section: Inbreeding Coefficientmentioning
confidence: 99%
“…С преустройството на селското стопанство в България, започва и реорганизация на селекционния процес, като за повишаване ефективността на селекционната дейност в животновъдството се създават неправителствени организацииразвъдни асоциации, към които се прехвърля тази дейност. Създадени са две организации, осъществяващи развъдна дейност със Среднородопската овца, Сдружение организация за развъждане на цигайски, романовски и местни породи овце в Република България (ОРЦМПО -Троян) и Асоциация за развъждане на Среднородопска, Каракачанска и Родопски цигай овце (АРСРККРЦО -Смолян За изследване на популационната структура и генетично разнообразие при дребните преживни животни все още масово се използва родословната информацията (Cortellari et al, 2022). В това отношение, пълнотата и качеството на педигрето са критични, тъй като грешките в педигрето могат да доведат до вземането на неправилни решения при съхранението на породите (Oliehoek & Bijma, 2009).…”
Section: въведениеunclassified